2013
DOI: 10.1021/bi401474x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the TOR-S6K Signaling Pathway in Maize (Zea mays L.). Pathway Activation by Effector–Receptor Interaction

Abstract: The primordial TOR pathway, known to control growth and cell proliferation, has still not been fully described for plants. Nevertheless, in maize, an insulin-like growth factor (ZmIGF) peptide has been reported to stimulate this pathway. This research provides further insight into the TOR pathway in maize, using a biochemical approach in cultures of fast-growing (FG) and slow-growing (SG) calli, as a model system. Our results revealed that addition of either ZmIGF or insulin to SG calli stimulated DNA synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Thus, growth stimulation induced by zmIGF and insulin in maize is due to the activation of TOR pathway involving phosphorylation of TOR and S6K. In addition, it was shown that zmIGF interact with a receptor located in the plasma membrane of maize cells (Garrocho-Villegas et al, 2013). Therefore, it is possible that OC kappa may interact with a receptor located in the plasma membrane leading to the production inositol 1,4,5 triphosphate (IP3) which induces realease of calcium from ER activating CDPKs na the latter may may activate enzymes that produced G6P and T6P which inhibit SnRK1 leading to TOR activation explaining, at least in part, the stimulation of growth observed in E. glopulus trees (see model in Fig.…”
Section: Oc Kappa Induced Increases In the Ievei Of Giucose And Trehamentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, growth stimulation induced by zmIGF and insulin in maize is due to the activation of TOR pathway involving phosphorylation of TOR and S6K. In addition, it was shown that zmIGF interact with a receptor located in the plasma membrane of maize cells (Garrocho-Villegas et al, 2013). Therefore, it is possible that OC kappa may interact with a receptor located in the plasma membrane leading to the production inositol 1,4,5 triphosphate (IP3) which induces realease of calcium from ER activating CDPKs na the latter may may activate enzymes that produced G6P and T6P which inhibit SnRK1 leading to TOR activation explaining, at least in part, the stimulation of growth observed in E. glopulus trees (see model in Fig.…”
Section: Oc Kappa Induced Increases In the Ievei Of Giucose And Trehamentioning
confidence: 99%
“…OC kappa-induced increase in the ievei of TOR-P and tor transcripts but not s6k transcripts OC kappa increases in the level of TOR-P from week 1 until the end of the experiment week 21with peaks at weeks 1, 2, 6, 12 and 16 compare to control plants. In this sense, it has been shown that an insulin-like growth factor (zmIGF) a well as bovine insulin induced an increase in cell division and growth in maize callus, phosphorylation of TOR in ser2448 and S6K in thr389 (Garrocho-Villegas et al, 2013). In addition, it was shown that rapamycin inhibited TOR and S6K phosphorylations.…”
Section: Oc Kappa Induced Increases In the Ievei Of Giucose And Trehamentioning
confidence: 99%
See 2 more Smart Citations
“…shown that zmIGF interact with a receptor located in the plasma membrane of maize cells (Garrocho-Villegas et al, 2013). Therefore, it is possible that OC kappa may interact with a receptor located in the plasma membrane leading to the production inositol 1,4,5 triphosphate (IP3) which induces realease of calcium from ER activating CDPKs na the latter may may activate enzymes that produced G6P and T6P which inhibit SnRK1 leading to TOR activation explaining, at least in part, the stimulation of growth observed in E. glopulus trees (see model in Fig.…”
Section: Oc Kappa Induced Increases In the Ievei Of Giucose And Trehamentioning
confidence: 99%